Overall cost optimization of prestressed concrete bridge using genetic algorithm - Aydin, Zekeriya; Ayvaz, Yusuf (KOREAN SOCIETY OF CIVIL ENGINEERS-KSCE, 2013)
Overall cost optimization of Prestressed Concrete (PC) bridges is investigated in this study. The purpose of this study is to determine the optimum span number and optimum cross-sectional properties of multi-span bridges. Considered bridge superstructure is constituted by adjacent simply supported pretensioned prestressed I-girders. Also, considered bridge substructure is constituted by single-column piers and rectangular spread footings. Span number, cross-section dimensions of prestressed girders and the area of Prestressing Steel (PS) are considered as design variables. PC girders, piers and footings are designed according to AASHTO Standard Specifications for Highway Bridges. A modified hybrid Genetic Algorithm (GA) is used for the optimum design. Working stress, ultimate strength, ductility limits, deflection, and geometry constraints are considered. Total cost of the bridge is taken as optimality criterion. A computer program is coded to perform optimum design and numerical examples from the application are designed. One of these examples is used in this paper. It is concluded that GA can be effectively used in the overall cost optimization of PC bridges.
Keywords: prestressed concrete; genetic algorithm; optimization; bridge; OPTIMUM DESIGN; FRAMES; Engineering